Persuasion Knowledge in the Marketplace: A Meta-Analysis - Martin Eisend; Farid Tarrahi (Journal of Consumer Psychology, 2021)
Since the introduction of the persuasion knowledge model more than 250.167emyears ago, many research studies have investigated how consumers' persuasion knowledge affects their reactions to persuasion attempts. While most results have shown that persuasion knowledge increases coping responses and leads to less favorable evaluations of marketer actions, the findings vary considerably, leaving researchers with a limited understanding of the substance and structure of persuasion knowledge effects and the conditions that explain their variability. To develop a better understanding of persuasion knowledge effects in the marketplace, this study builds on the concept of persuasion to predict responses to marketers' attempts to persuade consumers with different levels of persuasion knowledge. The study presents a meta-analysis of the findings in 148 papers and 171 distinct data sets. Persuasion knowledge effects can be viewed as substantial compared with persuasion attempts, but persuasion knowledge cannot suppress or eliminate persuasion effects in the marketplace, as it only reaches around 50% of the explanatory power of persuasion. Persuasion knowledge effects on evaluations and coping depend on the characteristics of the persuasion process. All persuasion elements that help consumers identify and better understand benefits not just for themselves, but also for marketers and how marketers realize their benefits—such as the use of personal communication, communication about unfamiliar products or products with experience attributes, and receiver experience—lead to less favorable effects for marketers. This paper's insights provide a new framework for persuasion knowledge effects in the marketplace, ideas for future research, and implications for researchers, consumers, policymakers, and marketers.
Keywords: 650; Persuasion knowledge; Persuasion; Consumer; Meta-analysis